Kisah Nabi Ismail dalam Perspektif Ilmu Tasawuf: Studi Kasus Keridhoan Orang tua Mahasiswi beasiswa KIP-K - Ayuni, Diah; Bakhri, Syamsul (Journal of Sufism and Psychotherapy, 2023)
This study examines the blessing of parents of Kip-K scholarship students on the requirements that must be done by scholarship recipients. Every Kip-K scholarship student is required to live in a boarding school for one year at the beginning of the course. In this case, the researchers used a qualitative method to track parents ' responses to the policy. Furthermore, the researcher applied the case study approach of the story of Prophet Ismail as a basis to make ridho that can be applied by student parents. The results showed that there are parents who are happy and there are also parents who have not been happy with their children living in boarding schools. Some say that living in a boarding school provides religious insight and as a way of moral formation of religious children. While some other parents claim to be worried about the circumstances and needs of their children while in boarding schools. Therefore, there is a need for prayer and effort so that parents give their blessing to scholarship recipients such as ridhonya Prophet Ismail who was slaughtered by his father at the behest of Allah SWT. Parents who are blessed are very influential on the development of children's learning so that children do not feel worried and feel safe for one year living in boarding schools. The role of children in convincing their parents to accept the policies that have been implemented is the main key in handling this case.